A proposal for an algorithm to count nodes using wireless technologies. (2015) - Gamess, Eric; Contreras, Manuel
Algorithms to count objects (people, animals, devices, vehicles, etc.) have interested the research community for a long time since they can be used as basic tools in the development of many applications. Up to now, most of the work done in this area is supported by turnstiles, digital cameras, video cameras, pneumatic road tubes, magnetic sensors, infrared beams, or other types of sensors. However, very few works have been developed using wireless communications to count nodes. In this paper, we introduce a new algorithm for counting nodes equipped with a wireless interface. To validate our proposal, we simulate the algorithm using OMNeT++/INET, a famous network simulation tool. Our simulations show that the proposed algorithm computes a number of nodes close to the real one, with a small number of messages and a short response time.